2018
DOI: 10.2147/ott.s167872
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of CXCL 11 inhibits colorectal cancer cell growth and epithelial-mesenchymal transition

Abstract: BackgroundThe poor prognosis of colorectal cancer (CRC) largely results from local invasion and tumor metastases. Epithelial-mesenchymal transition (EMT) is a key step in the progression of solid tumors and plays a vital role in tumor metastasis. Recent studies demonstrate that C-X-C motif chemokine 11 (CXCL11) is involved in various cancers’ progression. However, its biological activity in CRC needs deeper exploration.MethodsThe level of CXCL11 in CRC tissues and cell lines was determined using the quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 23 publications
2
30
0
Order By: Relevance
“…This chemokine is overexpressed in colorectal cancer tissues and cell lines, and its downregulation inhibits cell migration and invasion. Moreover, downregulation of CXCL11 has been shown to reduce colorectal cancer cell growth and metastasis in a xenograft model (24). Finally, the present study revealed that CCL4 expression was downregulated by lonidamine, DON and orlistat treatment.…”
Section: Discussionsupporting
confidence: 62%
“…This chemokine is overexpressed in colorectal cancer tissues and cell lines, and its downregulation inhibits cell migration and invasion. Moreover, downregulation of CXCL11 has been shown to reduce colorectal cancer cell growth and metastasis in a xenograft model (24). Finally, the present study revealed that CCL4 expression was downregulated by lonidamine, DON and orlistat treatment.…”
Section: Discussionsupporting
confidence: 62%
“…CXCL11 is overexpressed in CRC tissues and cell lines. Repression of CXCL11 significantly inhibited cell migration, invasion and epithelial-mesenchymal transition (EMT) (37). It was also reported that its downregulation can inhibit tumor angiogenesis in epithelial OV (38).…”
Section: Discussionmentioning
confidence: 96%
“…In this study, we found that patients with high abundance of intratumoral CXCL11 + cells in ltration had better survival and CXCL11 was found to have independent prognostic value in colon cancer. Considering that CXCL11-producing cells were a variety of heterogeneous cells [17] and the intercellular communication mediated by CXCL11 was complicated, the discoveries make sense [26,35].…”
Section: Discussionmentioning
confidence: 99%